Global, regional, and national burden of spinal cord lesion at neck level a systematic analysis of incidence, prevalence, YLDs with projections to 2046 - Zhang, Yi; Zhao, Weilun; Peng, Xiaoming; Yang, Fayun; Zong, Shaohui (Frontiers in Public Health, 2025)
BackgroundSpinal cord lesion at neck level imposes significant global morbidity, yet cervical-specific burden analysis remains limited.MethodsUsing Global Burden of Disease (GBD) 2021 data (1990–2021), we analyzed incidence, prevalence, and years lived with disability (YLDs) across 204 countries/territories, stratified by sex, age, socio-demographic index (SDI) regions, GBD super regions, and countries. Age-period-cohort (APC) model and Bayesian age-period-cohort (BAPC) model projected trends to 2046.ResultsIn 2021, global incidence was 306,568 (age-standardized incidence rate [ASIR] 3.78/100,000), prevalence 7.42 million (age-standardized prevalence rate [ASPR] 88.47/100,000), and YLDs 2.91 million (age-standardized YLDs rate [ASYLDR] 34.72/100,000). Males had higher burdens than females, with cases peaking at 45–64 years. Middle-SDI regions had the highest absolute cases (79,611 incidence), while high-SDI regions showed the highest age-standardized rates (ASRs) (ASIR 5.86/100,000). From 1990–2021, absolute cases rose, but ASRs declined. Projections predict rising absolute cases through 2046.ConclusionThis study reveals marked regional and demographic disparities in cervical spinal cord lesion burden. Targeted prevention and healthcare planning in high-burden regions are essential to address this global health challenge.